Cardiomyopathy complicated by left ventricular aneurysms in children. - Alday, L E (1976)
Ventricular aneurysms in children are unusual. Three patients with cardiomyopathy associated with angiographically proved left ventricular aneurysms in this age group are reported. Two of them were girls. The ages were 20 months, 7 years, and 14 years. Heart failure was present in all patients. There was radiological evidence of cardiomegaly in all three, and the electrocardiogram showed signs of necrosis in two of them. Selective left ventricular angiography disclosed generalized hypokinesis in all patients. One child had an aneurysm of the diaphragmatic wall. In another the aneurysm was localized in the muscular ventricular septum, causing severe subpulmonary stenosis by encroaching in the right ventricular outflow tract during systole. The third patient had an aneurysm of the left ventricular free wall partly encircling the left ventricle. The coronary arteries appeared normal in all cases. The clinical features of the underlying disease were not altered by the presence of the aneurysm except in the patient with the septal aneurysm and subpulmonary stenosis. In this patient the aneurysm was successfully resected.